2019
DOI: 10.1007/s00247-019-04505-2
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis of the ribs in children: a rare and potentially challenging diagnosis

Abstract: BACKGROUND Rib osteomyelitis is rare in children and can mimic other pathologies. Imaging has a major role in the diagnosing rib osteomyelitis. OBJECTIVE To evaluate clinical presentation and imaging findings in children with rib osteomyelitis. MATERIALS AND METHODS We performed a retrospective (2009-2018) study on children with rib osteomyelitis verified by either positive culture or pathology. We excluded children with multifocal osteomyelitis or empyema necessitans. We reviewed medical charts for clinical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
3
15
0
1
Order By: Relevance
“…Furthermore, the spread of this infection to surrounding tissues is responsible for significant morbidity and healthcare costs each year [1]. In high-income countries, acute osteomyelitis occurs in about 1of 800,000 children per year [2] but it is considerably more common in low-and middle-income countries [3]. In Morocco, osteomyelitis is more common among children [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the spread of this infection to surrounding tissues is responsible for significant morbidity and healthcare costs each year [1]. In high-income countries, acute osteomyelitis occurs in about 1of 800,000 children per year [2] but it is considerably more common in low-and middle-income countries [3]. In Morocco, osteomyelitis is more common among children [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the patient's mother did not notice chest swelling initially, and neither did the attending physicians. The general presentation of rib osteomyelitis has been reported as fever, chest or back pain, and an abscess [ 1 ]; however, other articles have reported that such findings are not always presented—instead, patients may display nonspecific clinical features [ 3 , 4 ]. Because of these nonspecific symptoms, the lack of local findings (such as redness and swelling), and the indolent lesion that often occurs in cases of rib osteomyelitis [ 3 ], it is difficult to diagnose this disease early.…”
Section: Discussionmentioning
confidence: 99%
“…The general presentation of rib osteomyelitis has been reported as fever, chest or back pain, and an abscess [ 1 ]; however, other articles have reported that such findings are not always presented—instead, patients may display nonspecific clinical features [ 3 , 4 ]. Because of these nonspecific symptoms, the lack of local findings (such as redness and swelling), and the indolent lesion that often occurs in cases of rib osteomyelitis [ 3 ], it is difficult to diagnose this disease early. This may lead to delays in treatment initiation compared with osteomyelitis affecting other parts, such as the long bones [ 2 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В диагностике остеомиелита ребра наряду с подробным сбором анамнеза (наличие травм в анамнезе, сопутствующей патологии), физикальным обследованием и результатами лабораторных исследований (клинический и биохимический анализы крови, прокальцитониновый тест в случае высокой и продолжительной лихорадки) важную роль играют методы визуализации [7]. Однако результаты визуализации (рентгенография, компьютерная томография) у таких детей могут быть неспецифическими и часто имитировать другие патологии, в особенности на ранних стадиях заболевания [8]. Именно поэтому чаще данную патологию принимают за опухоли типа саркомы Юинга и гистиоцитоз или тяжелое течение пневмонии [9].…”
Section: вопросы современной педиатрииunclassified